Isra mi raj mukjizat terbesar M. Mutawalli Asy-Sya rawi ; penerjemah, H. Salim Basyarahil ; penyunting, Iffa Karimah - Asy-Sya rawi, M. Mutawalli; Basyarahil, Salim, Haji; Karimah, Iffa (Gema Insani Press, 1994)
112 hlm. 18 cm.